(untitled) (Global Journal of Management and Business Research, 2023)
Businesses are increasingly challenged by increasing competition, changing customer preferences and, industry dynamics. Moreover, the proliferation of channels and customer touchpoints has added to the complexity of keeping up with these constant changes. Only organizations that are agile enough to understand, evaluate and react to these dynamic requirements can drive innovation and growth. Therefore, organizations must be creative in their consumer engagement strategy across the marketing funnel to enhance overall customer experience, measure the performance, and establish the loopback to refine the strategy. The following paper outlines concepts to help consumer businesses accelerate customer experience management. The objective of the paper is to lay out guiding principles that organizations can use as part of their business processes to create, deliver, and measure personalized customer experiences and drive growth, loyalty, and satisfaction. The paper will dive into the three most important pillars of building successful customer experiences -Design a Customer Experience Management Model, Activate across touchpoints, and Measure performance across touchpoints.